Child’s rights from the International Law perspective - Torrecuadrada García-Lozano, Soledad (2020)
In this article, the focus is the rights of children from the point of view of International Law. First, the historic evolution that happened in the twentieth century until the 1989 United Nations Convention. Nonetheless, the essential element that has emerged (the best interest of the Child) first appeared through jurisprudence in the XVIII Century. After studying the Convention, it is necessary to study the problems that formulate the Reserved matters aswell as underline its content, this paper will shift its focus onto the concretion of the superior interest of the minor, its relativism, la relevant of being heard and its application in different material aspects of family life, in which appeared.